Horizontal Gene Transfer and Gene Duplication of β-Fructofuranosidase Confer Lepidopteran Insects Metabolic Benefits. (19th March 2021) - Dai, Xiangping; Kiuchi, Takashi; Zhou, Yanyan; Jia, Shunze; Xu, Yusong; Katsuma, Susumu; Shimada, Toru; Wang, Huabing
Abstract: Horizontal gene transfer (HGT) is a potentially critical source of material for ecological adaptation and the evolution of novel genetic traits. However, reports on posttransfer duplication in organism genomes are lacking, and the evolutionary advantages conferred on the recipient are generally poorly understood. Sucrase plays an important role in insect physiological growth and development. Here, we performed a comprehensive analysis of the evolution of insect β-fructofuranosidase transferred from bacteria via HGT. We found that posttransfer duplications of β -fructofuranosidase were widespread in Lepidoptera and sporadic occurrences of β -fructofuranosidase were found in Coleoptera and Hymenoptera. β -fructofuranosidase genes often undergo modifications, such as gene duplication, differential gene loss, and changes in mutation rates. Lepidopteran β -fructofuranosidase gene ( SUC ) clusters showed marked divergence in gene expression patterns and enzymatic properties in Bombyx mori (moth) and Papilio xuthus (butterfly). We generated SUC1 mutations in B. mori using CRISPR/Cas9 to thoroughly examine the physiological function of SUC. BmSUC1 mutant larvae were viable but displayed delayed growth and reduced sucrase activities that included susceptibility to the sugar mimic alkaloid found in high concentrations in mulberry. BmSUC1 served as a critical sucrase and supported metabolic homeostasis in the larval midgut and silk gland, suggesting that gene transfer of β -fructofuranosidase enhanced the digestive and metabolic adaptation of lepidopteran insects. These findings highlight not only the universal function of β -fructofuranosidase with a link to the maintenance of carbohydrate metabolism but also an underexplored function in the silk gland. This study expands our knowledge of posttransfer duplication and subsequent functional diversification in the adaptive evolution and lineage-specific adaptation of organisms.